Rancang Bangun Aplikasi Penjualan Pada Mitra 10 Wiyung Surabaya - Christy, Agile Jaunty; Arifin, Mochammad; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: Mitra 10 Wiyung is a company engaged as a distributor of building materials. The sales process that occurs after the customer is finished selecting items, customers can pay to the cashier and received a bill of sale. After the sale process is completed, the company made sales summary. Then the manager checks sales data and if it is approved, then made the income statement. The problem that occurs is the company's difficulties in record sales summary for a data bill of sale is not neatly arranged. In addition, the company does not have a system to manage the stock so it cannot monitor the condition of the stock. To solve the above problems, this study using System Development Life Cycle that is Waterfall with that process; First, gather the information needs of the company. Second, designing software that attribute data structures, software architecture, interface design and software algorithms. Third, implement and test the unit. Fourth, perform system integration and testing of each function in the software. And the last is to perform the operation and maintenance of software. After analysis of the test results and evaluation of the system, it can be concluded that this study has been able to make a sales application on the Options in Mitra 10 Wiyung, then the application of this memorandum of sale, the sales summary and statement of income are neatly arranged and the system can be integrated with either. This application can also monitor the condition of the stocks held in the company.